Safety assessment of genetically modified foods - Huang, Kunlun (Springer, 2017)
This book introduces readers to food safety assessment research on Genetically Modified Organisms (GMOs). As is broadly known, the main concerns about GM foods' adverse effects on health are the nutrients, toxicity, allergenicity and unexpected effects. Before GMOs can be made commercially available, a comprehensive food safety assessment - taking these concerns into account - must first be performed. Exploring these aspects, the book is divided into two parts: the first part focuses on the safety assessment guidelines of the CAC, while the second highlights new methods used for the evaluation of GMOs' safety. Offering an essential, practical guide, it will be of interest to researchers and graduate students in the fields of food science and public health.
Keywords: Genetically modified foods -- Safety measures.; Genetically modified foods -- Risk assessment.; elektronické knihy; electronic books